1993
DOI: 10.1021/bi00074a009
|View full text |Cite
|
Sign up to set email alerts
|

Preferential intercalation at AT sequences in DNA by lucanthone, hycanthone, and indazole analogs. A footprinting study

Abstract: DNAase I footprinting has been used to probe the DNA sequence selectivity of the antitumor intercalating agents lucanthone (1), hycanthone (2), 6-chlorolucanthone (7), and four indazole analogs (IA-3-IA-6). The latter have a benzothiopyranoindazole chromophore substituted with a diethylaminoethyl side chain identical to that attached to the thioxanthenone chromophore of compounds 1, 2, and 7. IA-3 and IA-5 are lucanthone analogs bearing a methyl group at position 4, whereas IA-4 and IA-6 are hycanthone analogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…The apparent AT selectivity observed under our conditions is not consistent with previous NMR analyses (Feigon et al, 1984) which revealed a marginal G C preference for hycanthone binding to DNA. However, recent investigations by DNAaseI footprinting have fully confirmed the AT selectivity of binding to DNA of hycanthone and its metabolite (Bailly and Waring, 1993b). Needless to say, the observed A T selectivity of the two thioxanthenone derivatives may open the way for future design of AT reading agents based on intercalative binding.…”
Section: (Drp"ly(da) P O L~( D T ) /~~P O L~( D G )mentioning
confidence: 98%
“…The apparent AT selectivity observed under our conditions is not consistent with previous NMR analyses (Feigon et al, 1984) which revealed a marginal G C preference for hycanthone binding to DNA. However, recent investigations by DNAaseI footprinting have fully confirmed the AT selectivity of binding to DNA of hycanthone and its metabolite (Bailly and Waring, 1993b). Needless to say, the observed A T selectivity of the two thioxanthenone derivatives may open the way for future design of AT reading agents based on intercalative binding.…”
Section: (Drp"ly(da) P O L~( D T ) /~~P O L~( D G )mentioning
confidence: 98%
“…Evidently this type of aminoalkylamino side chain, frequently encountered in intercalating drugs (e.g. quinacrine, lucanthone and hycanthone [27]) cannot be responsible for the primary sequence recognition. The lack of any strong sequence selectivity on the part of the two drugs is likely to account (at least partially) for their triple-helix stabilizing property.…”
Section: G C G G C G C G T C a T T T G A T A T G A T G C G C C C C G mentioning
confidence: 99%
“…Included in this class of APE-1 inhibitors is a series of arylstibinic acids (Figure 9; compounds 13755 and 13743), which although potent at nanomolar concentrations in biochemical experiments, lacked activity in cells [81]. Lucanthone, which inhibits APE-1/REF-1 activity and binds to the protein [82], also interacts with other cellular targets, including DNA via intercalation [83], so the mechanism of action remains uncertain. E3330 (Figure 9), which inhibits APE-1 endonuclease activity at low micromolar concentrations, was originally identified as a specific inhibitor of APE-1 redox activity [84].…”
Section: Potential Drug Targets To Overcomementioning
confidence: 99%